How to maximize the therapeutic effect of exosomes on skin wounds in diabetes mellitus: Review and discussion - Dong, Jia; Wu, Bin; Tian, Weidong (Frontiers in Endocrinology, 2023)
Chronic skin wound healing, especially in diabetes mellitus, is still an unsolved field. Although many efforts have been made to treat diabetic skin wounds, all these strategies just achieved limited effectiveness. Nowadays, a great number of studies have shown that exosomes might be a promising approach for treating diabetic wounds. Many studies and reviews have focused on the investigation and discussion of the effectiveness and mechanism of exosomes. However, how to maximize its value in the treatment of skin wounds in diabetes mellitus need to think about deeply. In this review, we reviewed and discussed the aspects that could be further improved in this process, including finding the better source of exosomes, engineering exosomes, mediating dosage and frequency, and combining more efficient delivery methods. This review provided an overview and idea for what we can do to improve the therapeutic effect of exosomes on skin wounds in diabetes mellitus. Only by combining all the factors that affect the effectiveness of exosomes in diabetic wound healing can we further promote their clinical transformation.